2012
DOI: 10.1016/j.annemergmed.2011.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Serum Glial Fibrillary Acidic Protein Breakdown Products in Mild and Moderate Traumatic Brain Injury Are Associated With Intracranial Lesions and Neurosurgical Intervention

Abstract: Objective This study examined whether serum levels of GFAP breakdown products (GFAP-BDP) were elevated in mild and moderate TBI compared to controls and if they were associated with traumatic intracranial lesions on CT scan (+CT) and having a neurosurgical intervention (NSI). Methods This prospective cohort study enrolled adult patients presenting to three Level 1 Trauma Centers following blunt head trauma with loss of consciousness, amnesia, or disorientation and a GCS 9–15. Control groups included normal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
259
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 283 publications
(287 citation statements)
references
References 65 publications
15
259
0
4
Order By: Relevance
“…[25][26][27] Our findings are also consistent with previous reports in terms of predictive power and measured levels of serum GFAP in TBI. 4 We found that serum GFAP-BDP Odds ratio (GOS-E £ 7)…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…[25][26][27] Our findings are also consistent with previous reports in terms of predictive power and measured levels of serum GFAP in TBI. 4 We found that serum GFAP-BDP Odds ratio (GOS-E £ 7)…”
mentioning
confidence: 96%
“…GFAP-BDP levels were greater in patients with CT scans positive for traumatic lesions (0.26 -0.41 ng/mL vs. 2.88 -3.74 ng/mL; p < 0.01), which is consistent with the previous findings of . 4 The ability of GFAP-BDP to discriminate between the likelihood of an unfavorable 6 month outcome, measured by the AUC, was adequate at 0.74, and the ability of GFAP-BDP to discriminate between the likelihood of a full recovery was 0.65. The optimal GFAP-BDP cutoff value was 0.68 ng/mL for identifying patients who failed to return to pre-injury baseline, and resulted in a 21.61 OR for a positive head CT and a 2.07 OR for failure to return to pre-injury baseline.…”
mentioning
confidence: 98%
See 3 more Smart Citations